PENERAPAN MODEL PEMBELAJARAN PEER LED GUIDED INQUIRY (PLGI) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA MATERI KESETIMBANGAN KELARUTAN KELAS XI MIA SMA NEGERI 3 PEKANBARU - Dermawan, Ibnu; Rery, R.Usman; holiwarni, Betty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aimed to increase students achievement implementation of peer led guided inquiry (PLGI) on subject equilibrium solubility in XI MIA SMAN 3 Pekanbaru. The type of this research is experimental research with randomized control group pretest-posttest design. Subject of this research are XI MIA 4 as the experimental class, XI MIA 5 as the control class which were determined randomly after conducting normality and homogeneity test. The experimental group was treated with implementation of peer led guided inquiry (PLGI) while the control group without implementation of peer led guided inquiry (PLGI). The data analysis to test the hypothesis was using t-test right side. Based on the data analysis, it is obtaine tcount = 4,99 and ttable = 1,67 with α=0,05, dk = 57, tcount > ttable is 4,99 > 1,67, It’s mean implementation of peer led guided inquiry (PLGI) can improve students achievement on the subject equilibrium solibility in XI MIA SMA Negeri 3 Pekanbaru. The influence implementation learning model peer led guided inquiry (PLGI) to improvement of the student achievement as high as 30,4%.Keywords: Peer Led Guided Inquiry (PLGI), Learning Achievement